A coupled Smoothed Particle Hydrodynamics-Volume Compensated Particle Method (SPH-VCPM) for Fluid Structure Interaction (FSI) modelling. (15th December 2020) - Ng, K.C.; Alexiadis, A.; Chen, Hailong; Sheu, T.W.H.
Abstract: A new unified particle model that couples the Smoothed Particle Hydrodynamics (SPH) and a discontinuous approach known as the Volume Compensated Particle Method (VCPM) is developed to solve Fluid Structure Interaction (FSI) problems involving large deformation. Unlike the model that couples the Smoothed Particle Hydrodynamics and the Discrete Element Method (i.e. SPH-DEM) in which the applicable Poisson's ratio of the solid material should be less than certain critical values, the current unified particle model is able to model solid materials of large Poisson's ratio by using only axial interaction between solid particles. The coupling between SPH and VCPM is accomplished by treating the solid particles of VCPM at the solid-fluid interface as dummy particles in SPH. This paper presents the first SPH-VCPM coupled method for FSI with comprehensive validations. The VCPM solver is firstly verified for solving static and dynamic solid mechanics problems. Then, the proposed solver is used to solve several FSI problems involving free surface, i.e. water column on an Aluminum plate, flow under an elastic gate, dam break problems involving flexible structures and deformation of flexible structure in a rolling oil tank. The SPH-VCPM results match well with the published numerical results obtained from the literature. Highlights: A unified particle method is developed for solving FSI problems with free surface. This model can handle FSI problem with elastic body of a wider range of Poisson ratio. The coupling procedure at the solid-liquid interface is shown. The FSI results involving free surface are validated with those of other methods. The spatial order of convergence for the VCPM method is reported.